Effect Of Chemical Treatment On Rice Husk (RH) Reinforced Polyethylene (PE) Composites - Md. Rezaur, Rahman; Md. Nazrul, Islam; Md. Monimul, Huque; Sinin, Hamdan; Abu Saleh, Ahmed (BioResources, 2010)
In this study rice husk reinforced polyethylene composites and their test specimens were manufactured using a single screw extruder and an injection molding machine, respectively. Raw rice husk was chemically treated with benzene diazonium salt in alkali, acidic, and neutral media, in order to improve in the mechanical properties. The mechanical properties of the composites prepared from alkaline media treated rice husk were found to increase substantially compared to those of acidic media, neutral media, and untreated ones. However, the values for the alkaline media treated rice husk-PE composites at all mixing ratios were found to be higher than those of treated acidic media, treated neutral media, and untreated rice husk composites respectively. The SEM micrographs reveal that interfacial bonding between the treated filler and the matrix has significantly improved, suggesting that better dispersion of the filler into the matrix was achieved upon treatment of rice husk. Based on filler loading, 35% filler reinforced composites had the optimum set of mechanical properties among all composites manufactured.